Membangun Kerangka Dasar Sistem Informasi Kelapa Sawit Rakyat Kecamatan Kuok Kabupaten Kampar - Joko Risanto; Fatayat; Zaiful Bahri; Rahmad Kurniawan; Teguh Sujana; Finanta Okmayura (Prosiding SISFOTEK, 2025)
Since the 1980s, palm oil has been a special commodity for Indonesia because it provides the largest income for the country, providing economic turnover for rural communities. Although palm oil has become a special commodity for Indonesia, it cannot be denied that until now many problems are still faced by palm oil farmers, namely, difficulties in fertilizer, inadequate human resources of palm oil farmers, land conflicts and production results rejected by palm oil mills. The local government does not have valid data on smallholder oil palm plantations, causing local government planning and policies regarding the distribution of subsidized fertilizers and assistance with superior oil palm seeds to farmers to be inaccurate. In order to increase the low productivity of smallholder oil palm plantations, it is necessary to immediately organize the management of smallholder oil palm plantations based on digital data so that the government or related institutions can make plans and decisions about increasing the capacity of oil palm farmers based on valid, easy and fast to access information. Digital transformation in the upstream activities of the oil palm plantation supply chain is the first step in realizing modern smallholder plantations. This study applies an information system framework analysis approach to develop an information system for smallholder oil palm plantations in Kuok District, Kampar Regency. Identifying management challenges, analyzing information technology infrastructure, understanding basic business process concepts, developing systems, and developing desired business application characteristics provide a basic framework for an ideal smallholder oil palm plantation information system for village, sub-district, and regional governments. The analysis results in a prototype application that displays farmer profile information, plantation characteristics, and production results. The information can be accessed at three managerial levels: the village, sub-district, and district government levels (Plantation Office).